Impact of Typeface and Colour Combinations on LCD Display Legibility - Gregor Franken; Maruša Pangerc; Klementina Možina (Emerging Science Journal, 2020)
The evolution of high resolution displays, especially liquid crystal displays (LCD), which are among the most commonly used ones, has contributed to a larger number of display readers. Regardless of high resolutions, problems in the legibility of typefaces still occur. Many typefaces may well be readable in print, but cause more difficulties when being read on displays. The aim of this study was to examine the influence of colour contrast on the legibility on LCDs to establish which type style is appropriate for a coloured text to be legible. Two different typefaces specially designed for display use were tested in a satisfactory light-dark contrast of five different colour combinations. The reading speed and fixations were analysed with an eye-tracking device Tobii 120X. Different texts were displayed on an LCD display. The results showed that the selection of a particular colour combination and contrast greatly affects the reading speed and legibility. Less visible colour combinations of text and background were read more slowly than the more contrasting or visible ones in both typefaces. At both typefaces, it was seen that at a slower reading speed, more fixations were needed and vice-versa. A transitional typeface gave a faster reading speed than a sans-serif typeface. An appropriate contrast, colour combination and used typography can facilitate legibility on displays. Doi: 10.28991/esj-2020-01243 Full Text: PDF